EU–Africa Migration Compacts and the Coloniality of Border Governance: A Critical Analysis of Externalization Practices (International Journal of Scientific Research and Management (IJSRM), 2025)
This study critically examines the European Union’s (EU) externalization of border controls into African territories, situating the analysis within the broader context of EU–Africa migration compacts. Adopting a qualitative research design, the study draws primarily on secondary sources, including policy documents, scholarly literature, official reports, and recent case studies. Using postcolonial theory as the analytical lens, it interrogates the historical continuities, power asymmetries, and neocolonial dynamics underpinning contemporary EU migration governance. The analysis reveals how policies framed as cooperative security and development partnerships frequently undermine African sovereignty, reinforce dependency, and shift humanitarian responsibilities onto resource-constrained African states. The study also explores the potential of the Global Compact for Safe, Orderly and Regular Migration (GCM) and inclusive talent partnerships as alternative frameworks for more equitable migration governance. However, it finds that without substantive policy reform particularly the dismantling of conditionalities, the reframing of skill definitions, and the centralization of African priorities such initiatives risk reproducing the very asymmetries they are intended to address. The paper concludes by advocating for the operationalization of genuinely reciprocal, development-oriented migration frameworks that balance security imperatives with human rights protections and shared responsibility.